2021
DOI: 10.1101/2021.03.22.21254120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiplex Antibody Analysis of IgM, IgA and IgG to SARS-CoV-2 in Saliva and Serum from Infected Children and their Close Contacts

Abstract: COVID-19 affects children to a lesser extent than adults but they can still get infected and transmit SARS-CoV-2 to their contacts. Field deployable non-invasive sensitive diagnostic techniques are needed to evaluate the infectivity dynamics of the coronavirus in pediatric populations and guide public health interventions. We evaluated the utility of high-throughput Luminex-based assays applied to saliva samples to quantify IgM, IgA and IgG antibodies against five SARS-CoV-2 spike (S) and nucleocapsid (N) ant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…Using saliva RDT, despite lower general sensitivity compared to both saliva RT-PCR and nasopharyngeal RDT, based on RT-PCR Ct/viral load values almost all presumed infectious individuals could be detected, however this result could not be compared to nasopharyngeal swab virus culture in the current study. Saliva is a complex material shown to have comparable or slightly lower viral load to nasopharyngeal sample [ 13 ], it also contains SARS-2 specific antibodies [ 14 ] and different viral kinetics compared to nasopharynx which might explain the lower performance in the tested population. Furthermore, we have evaluated this test on non-hospitalized patients and a study found correlation of more severe disease with higher viral load in saliva [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using saliva RDT, despite lower general sensitivity compared to both saliva RT-PCR and nasopharyngeal RDT, based on RT-PCR Ct/viral load values almost all presumed infectious individuals could be detected, however this result could not be compared to nasopharyngeal swab virus culture in the current study. Saliva is a complex material shown to have comparable or slightly lower viral load to nasopharyngeal sample [ 13 ], it also contains SARS-2 specific antibodies [ 14 ] and different viral kinetics compared to nasopharynx which might explain the lower performance in the tested population. Furthermore, we have evaluated this test on non-hospitalized patients and a study found correlation of more severe disease with higher viral load in saliva [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most dramatic example of this is the human papillomavirus (HPV) vaccine, which provides 99% protective immunity in the vaginal tract, even though the vaccine is a conventional intramuscular immunization and elicits circulating IgG. For SARS‐CoV‐2 previously infected individuals, the titers of circulating IgG correlate with saliva IgG, 56,190,197 and the correlation was sustained over a period of 9 months 56 . Correlation between circulating IgA and saliva IgA in previously infected individuals was also substantial over a 9‐month period 56 .…”
Section: Antibody Durability To Sars‐cov‐2 Infection or Covid‐19 Vacc...mentioning
confidence: 99%
“…Using saliva RDT, despite lower general sensitivity compared to both saliva RT PCR and nasopharyngeal RDT, most infectious individuals could be detected, however this result was not compared to nasopharyngeal virus culture. Saliva is a complex material shown to have comparable or slightly lower viral load to nasopharyngeal sampling sites (8), it also contains SARS-2 specific antibodies (9) and different viral kinetics compared to nasopharynx which might explain the lower performance in the tested population. We have evaluated this test on non-hospitalized patients; a study found correlation of more severe disease with higher viral load in saliva (10).…”
Section: Discussionmentioning
confidence: 99%